2020
DOI: 10.21108/ijoict.2020.61.489
|View full text |Cite
|
Sign up to set email alerts
|

WhatsApp Chat Visualizer: A Visualization of WhatsApp Messenger’s Artifact Using the Timeline Method

Abstract: <p>WhatsApp is a medium that everyone can use to interact and to share information effectively and efficiently. However, it can be misused for criminal activities. Analyzing WhatsApp' artifacts is quite challenging as the suspect may have a lot of random conversational data to be considered. This makes it difficult for the trial process to obtain digital traces that can be identified in malicious activities such as knowing who was involved when the conversation was held and the timespan. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…Both studies highlighted the use of forensic visualization to enhance forensic analysis tasks for mobile forensics. Shidek et al [65] demonstrated timeline graph visualization to display data from WhatsApp chat conversations. The utility of the tool was evaluated through questions derived from forensic analysis goals: what cyber incident occurred, who was involved in the incident, and where, when, and how the incident occurred.…”
Section: A Role Of Visualization For Forensic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Both studies highlighted the use of forensic visualization to enhance forensic analysis tasks for mobile forensics. Shidek et al [65] demonstrated timeline graph visualization to display data from WhatsApp chat conversations. The utility of the tool was evaluated through questions derived from forensic analysis goals: what cyber incident occurred, who was involved in the incident, and where, when, and how the incident occurred.…”
Section: A Role Of Visualization For Forensic Analysismentioning
confidence: 99%
“…The InfoVis data types were adopted from [53], while the list of visualization techniques was adopted from a survey conducted in [68]. [64], [72], [51], [59], [60], [65], [62] From Table II, we can see that forensic visualization was applied in various case studies, including recent computing trends, such as the Internet of Things. This finding accords with an earlier observation in [52], which showed various applications of InfoVis.…”
Section: B Research Trends Of Forensic Visualization For Forensic Ana...mentioning
confidence: 99%
“…Pemisahan teks untuk komunikasi asinkron dengan pipeline [6], Pencarian kata kunci dengan indek untuk audit forensik dapat dilakukan [7]. Data komunikasi WAG ditelusuri dengan Timeline dalan menggali informasi yang penting seperti informasi tentang siapa yang terlibat kapan dan jam berapa percakapan dilakukan [8]. Secara analisis kuantitatif dan kualitatif dengan paradigma pragmatis data komunikasi WAG bisa diekplorasi [9].…”
Section: Pendahuluanunclassified
“…Pada penelitian ini menggunakan konsep timeline [8] untuk mengetahui interaksi waktu tertentu sedangkan penelitian ini yang lebih diekplorasi untuk melihat waktu respon terbaik dalam penyampaian pesan pada WAG "Gurauan " pada rentang waktu november 2019 sampai maret 2021. Analisis sentimen yang dilakukan [12] dengan Sentimental teks Transliterasi untuk Malayalam text.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation